ANALISIS IMPLEMENTASI GAYA KEPEMIMPINAN DEMOKRATIS KEPALA SEKOLAH DI LEMBAGA PENDIDIKAN - Aisyah, Siti; Sania, Sarah; Habibi, Ikbal; Mu’alimin, Mu’alimin (Lembaga Penelitian UM Metro, 2024)
This research discusses the analysis of the implementation of school principals' democratic leadership style in educational institutions. Democratic leadership style is the ability to influence other people to cooperate in achieving the goals that have been set by means of various activities that will be carried out jointly determined by the leader and subordinates. This article discusses the meaning of school principal leadership, the meaning of a school principal's democratic leadership style, and the factors that influence a school principal's leadership style. The method used in this research is a literature review or literature study. Literature study is an information gathering technique that is carried out by reviewing several articles that match the title of the discussion. The data collection process was carried out by searching for various articles on Google Scholar and analyzed in the form of a simplified approach. and there were 7 articles in this research which were then reviewed and packaged in the form of a literature review matrix. The results of the analysis show that the democratic leadership style has been widely applied by school principals in educational institutions, for example in making decisions, in improving teacher professionalism, teacher performance, teacher work discipline, student discipline, and in improving student learning outcomes and the quality of graduates.